FOLK ARTS AND CRAFTS OF THE ADIGES AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF THE REGION (2010s) - Belozerova, Marina Vital'evna (History, Archeology and Ethnography of the Caucasus, 2024)
The Circassians artistic crafts revival and development, the Republic of Adygea authorities experience in their preservation, he modern trends identification are the article goals. This topic is part of a set of problems on the different ethnic groups history of and the preservation of their identity. The results of the study of this issue are important. They identify the region development resource and help make management decisions taking into account the economic, social, ethnic, and cultural regional interests.The systemic and process methodological approaches principles made it possible to explore the views of government bodies of the Republic of Adygea, civil society, and to explore the communication links system . These issues were considered as a principle of «security» conception. The nest sampling research reception made it possible to study problems according to chronological (2010s) and territorial (Republic of Adygea) by chronological sections.Materials from the National Archive of the Republic of Adygea, Information and Analytical Department of the State Council – Khase of the Republic of Adygea, legislative acts were used for the first time.The causes of problems in the field of folk arts and crafts are discussed in the article. A set of measures to solve problems for the folk artistic crafts preservation and development was developed by government authorities, civil society representatives and craftsmen. For example, in regional brand creation and including traditional crafts in the concept of sustainable development and Republic recreational potential unlocking
Keywords: traditional culture; folk arts and crafts; sustainable development; Circassians; Republic of Adygea